RPP DALAM KURIKULUM PAI - Siti Aminah; Firda Magfirotus Sholehah; Ainun Zahro Hidayati; Nanang Budianto (PT. Hasba Edukasi Mandiri, 2026)
Lesson Plan (RPP) is an essential component in the learning process, especially in Islamic Religious Education (PAI). This study aims to describe the importance of lesson plans in the PAI curriculum, the objectives of learning palnning, the steps in preparing lesson plans, the principles of preparation, and their functions of lesson plans in improving the quality of learning. The research method uses is a literature study method by collecting data from various sources such as books, scientific journals, and relevant educational regulations. The results show that lesson plans have a strategic role as guidelines for teachers in palnning, implementing, and evaluating learning activities so that the learning procces can run systematicallly, effectifelly, efeciently, and in accordance with educational goals. A well-prepared lesson plan can also support active, creative, and student-orinted learning by devoloping cognitive, affective, and psycomotor aspects. In addition, in Islamic Religius educatin, lesson plans play an important role in shaping students character and noble morals (akhlaqul Karimah)